Culture to Serve Barometer Sustainability of North Sumatera and HANKAMNAS Development in Indonesia - Indra Jaya (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
Malay culture is a unifying tool for the diversity of ethnicity, religion and strata of social life in North Sumatra. This can be traced from: (1) In terms of religious practice manifested in the form of tolerance in carrying out social life among the adherents. (2) In terms of social life, the ability of Malay culture to internalize the diversity of tribes and customs in the differences in the life of social institutions. (3) In terms of community culture, showing the characteristics of millennial generation cultural values ​​as a social phenomenon is actually more likely to be negative. "(4) From the economic side, although Malay culture has very little influence in determining the HANKAMNAS barometer in Indonesia, but the influence Malay culture is not a factor that causes stunted development in northern Sumatra. " (5) From a political standpoint, Malay Culture positively influences the political situation in North Sumatra and at the same time Cultural change by the use of social media negatively affects the political situation in North Sumatra towards the sustainability of development so that it Impacts the Declining of HANKAMNAS in Indonesia "